2013
DOI: 10.1007/s12263-012-0329-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of genes involved in lipid metabolism in obese subjects with unfavourable phenotype

Abstract: Obesity (BMI C30 kg/m 2 ) increases the risk of developing lifestyle-related diseases. A subgroup of obese individuals has been described as ''metabolically healthy, but obese'' (MHO). In contrast to at-risk obese (ARO), the MHO phenotype is defined by a favourable lipid profile and a normal or only slightly affected insulin sensitivity, despite the same amount of body fat. The objective was to characterize the metabolic phenotype of MHO subjects. We screened a variety of genes involved in lipid metabolism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 29 publications
7
35
0
1
Order By: Relevance
“…In agreement with our findings, no differences in the expression of inflammatory genes in adipose tissue or PBMC between metabolically obese healthy and metabolically abnormal obesity groups have been found in recent studies (Catalán et al 2007a;Gómez-Ambrosi et al 2014;Telle-Hansen et al 2013). Moreover, we have identified that the upregulation of gene expression levels of most of the novel adipokines in PBMC is associated with their circulating concentrations, suggesting the contribution of these types of cells to the increased circulating levels in obesity states.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our findings, no differences in the expression of inflammatory genes in adipose tissue or PBMC between metabolically obese healthy and metabolically abnormal obesity groups have been found in recent studies (Catalán et al 2007a;Gómez-Ambrosi et al 2014;Telle-Hansen et al 2013). Moreover, we have identified that the upregulation of gene expression levels of most of the novel adipokines in PBMC is associated with their circulating concentrations, suggesting the contribution of these types of cells to the increased circulating levels in obesity states.…”
Section: Discussionsupporting
confidence: 93%
“…Its action has also been suggested to be linked with insulin secretion and insulin action (Kraemer and Shen 2002). Expression of this gene has also been described in PBMCs, where its level was found to be reduced in ''at risk'' obese subjects (Telle-Hansen et al 2013). Interestingly, in the present study, we show that young CR animals exhibited higher Lipe mRNA levels in PBMCs and similarly in iWAT.…”
Section: Discussionsupporting
confidence: 78%
“…Adiponectin is a protein produced by adipose tissue and has known insulin--sensitizing [283] and anti--inflammatory [7] properties. Our adiponectin results are similar to those reported by Telle--Hansen et al, who had an equivalently sized cohort and used similar classification criteria to identify MHO individuals [273]. However, our findings do not agree with those of other studies showing that MHO individuals had higher adiponectin levels compared to MUO individuals [284--288].…”
Section: Discussionsupporting
confidence: 50%
“…While such an approach has not been used to study MHO, this is warranted given that the expression of lipogenic genes was recently shown to differ between MHO and MUO individuals [273]. As such, we expect that using a FA profiling approach will generate novel insight to help understand if FAs contribute to the reduced inflammatory state seen in MHO individuals.…”
Section: Introductionmentioning
confidence: 99%